Comparative epidemiology of six respiratory pathogens among children aged 28 days to 14 years with acute respiratory infections in coastal Xiamen and inland Linxia, China: a multicenter retrospective study - Xingxiang Zheng; Hongmei Ma; Jiali Cao; Jumei Liu; Rui Guo; Qunshan Xu; Xiaoli Chen; Shiqiang Han; Huiming Ye (Frontiers in Public Health, 2026)
Objective Acute respiratory infections are a major public health problem in children. The epidemiology of pediatric respiratory pathogens has shifted in recent years. This study aimed to compare the epidemiological patterns of six common respiratory pathogens among children with acute respiratory infections (ARI) in Xiamen and Linxia, China. Methods This retrospective study included 5,835 children with ARI from December 2024 to November 2025. Oropharyngeal swabs were tested for rhinovirus (RV), respiratory syncytial virus (RSV), influenza A virus (Flu A), influenza B virus (Flu B), adenovirus (ADV), and Mycoplasma pneumoniae (MP) using multiplex RT-PCR. Detection rates were compared by region, sex, age group and season. Results Overall, 3,143 samples (53.9%) were positive; 290 (5.0%) had co-detections. RV (23.8%), RSV (20.2%) and Flu A (8.8%) were most frequently detected. Positivity was higher in Linxia than in Xiamen (65.4% vs. 49.0%; p < 0.001). After adjustment, Linxia remained associated with higher odds of detection (aOR 1.86, 95% CI 1.65–2.10). Detection was also associated with male sex, toddler/preschool age and autumn/winter seasons. Conclusion RV, RSV and Flu A were the most frequently detected pathogens in both regions. The findings indicate regional, age-related and seasonal heterogeneity, supporting locally tailored surveillance and prevention planning.